Hubungan Motivasi dan Beban Kerja terhadap Kinerja Perawat Rawat Inap di RSUD Barru - Ichsan Trisutrisno (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Nurse performance is an important indicator of service quality and is influenced by internal factors such as work motivation and external factors such as workload. An imbalance between job demands and available resources can reduce the quality of nursing care in inpatient wards. This study aimed to analyze the relationship between work motivation and workload with nurse performance in the inpatient wards of Barru Regional General Hospital. This study employed a quantitative method with a descriptive-analytic design and a cross-sectional approach. The sample consisted of 66 nurses selected through simple random sampling. Data were collected using questionnaires on work motivation, workload, and nurse performance, and were analyzed using the chi-square test. The results showed that most nurses had high work motivation (56.1%), heavy workload (69.7%), and good performance (62.1%). There was a significant relationship between work motivation and nurse performance (p = 0.032), as well as between workload and nurse performance (p = 0.045). Multivariate analysis showed that work motivation and workload were simultaneously and significantly associated with nurse performance, with work motivation as the most dominant factor. These findings emphasize that integrated management of work motivation and workload is an important strategy to improve nurse performance, service quality, and patient safety in inpatient wards.